2021
DOI: 10.1016/j.ekir.2021.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-Phenotype Correlation in WT1 Exon 8 to 9 Missense Variants

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…However, variants involving other sites in WT1 result in a mild phenotype (including FSGS) (28). Indeed, in this study, all WT1 variants were outside the DNA-binding site and led to slower progression compared with previous findings in patients with Denys–Drash syndrome (29).…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…However, variants involving other sites in WT1 result in a mild phenotype (including FSGS) (28). Indeed, in this study, all WT1 variants were outside the DNA-binding site and led to slower progression compared with previous findings in patients with Denys–Drash syndrome (29).…”
Section: Discussionsupporting
confidence: 49%
“…However, variants involving other sites in WT1 result in a mild phenotype (including FSGS) (28). Indeed, in this study, all WT1 variants were outside the DNA-binding site and led to slower progression compared with previous findings in patients with Denys-Drash syndrome (29). In previous studies, univariate analyses indicated that the renal prognosis was good in patients with the tip variant of FSGS (10,(20)(21)(22) and poor in patients with the collapsing variant (10,20,21,30).…”
Section: Discussionsupporting
confidence: 40%
“…According the study reported by Eujin Park ( 15 ) in 2020, WT1 was the most commonly mutated gene in CNS, followed by NPHS1, COQ3 and LAMB2. While in the study by Nagano C from Japan ( 23 ), NPHS1, LAMB2 and WT1 was the most commonly gene detected in CNS. So, the genetic detection rate and the leading genes in CNS vary among different countries and district worldwide.…”
Section: Discussionmentioning
confidence: 91%
“…In this case series and literature review, we were unable to refine the clinical phenotypes with the specific WT1 mutation analyses which have become more available in the recent years. These studies have been able to categorize the various mutations with broader clinicopathologic correlations (39). Over 30 mutations or missense variants of the WT1 protein have been analyzed, reported, and correlated with phenotypes that include proteinuria, ESKD, genital anomalies, and Wilm's tumor (13).…”
Section: Discussionmentioning
confidence: 99%